The Impact of Process Genre Based Approach in students Written Competence (2017)
ABSTRACT: This work was an action research project developed with the intention of understanding the impact of Process Genre based Approach in sixth graders’ English writing competence at Alfred Binet school. The information for this project was collected through journals, student’s writings, and cartographies; and the analysis of all this gathered information showed students had difficulties to write in English. After the implementation of the approach mentioned before, it was found three outcomes: 1. The approach fostered student’s positive attitude in English classes; 2. Student’s opinion about writing changed favorably; and 3. Students writing improved considerably in their last writings of the project.